Kansas as a dairy state - Shull, C.W. (My University, 1897)
Introduction: While Kansas as a state is rapidly taking high rank among her sister states by reason of her natural wealth, her agricultural and stock interests, and her intelligent energetic people; she does not as yet rank high as a dairy state. There is no just cause for this. While reasons may be given as to why Kansas has fallen behind in the onward march of dairy progress, there should be no grounds for these reasons and there will be none when Kansans are educated to see and follow the course which is for their best interest. The school of experience is a large school, and there only do many men learn. The lack of interest, in the past, in this important branch of agricultural industry may be due to several causes. In the first place the state is naturally adapted to stock raising, and the production of beef has been practically the only line along which the cattle industry has been conducted. The rich inviting prairie soil gave great encouragement to grain-growing, which, followed in connection with stock raising was found very profitable. Dairying, as a distinct branch of agriculture did not attract great attention. This was largely due to the fact that practically no interest in the subject had yet been aroused, and also that farming was conducted on too extensive a scale, as it is in fact yet to-day.
Citation: Shull, C.W. Kansas as a dairy state. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Kansas; Dairy; Theses; Manuscripts (documents)